2019
DOI: 10.1097/md.0000000000015453
|View full text |Cite
|
Sign up to set email alerts
|

Impact of renal dysfunction on surgical outcomes in patients with aortic dissection

Abstract: Preoperative renal dysfunction is associated with mortality in patients who undergo coronary artery bypass graft and valve surgery. However, the role of preoperative renal dysfunction in type A aortic dissection (TAAD) remains unclear. This study aimed to evaluate the impact of preoperative renal dysfunction on the outcome of surgical intervention in patients with TAAD. We retrospectively studied the outcomes of 159 patients with TAAD who were treated at a tertiary referral hospital between 2005 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…These results show that an increase of Cr before the operation can increase the mortality after operation. The results of this study also confirmed that preoperative Cr increase is an independent risk factor for postoperative death (17). Wang et al's research shows that preoperative renal insufficiency is closely related to the increase of postoperative complications.…”
Section: Discussionsupporting
confidence: 81%
“…These results show that an increase of Cr before the operation can increase the mortality after operation. The results of this study also confirmed that preoperative Cr increase is an independent risk factor for postoperative death (17). Wang et al's research shows that preoperative renal insufficiency is closely related to the increase of postoperative complications.…”
Section: Discussionsupporting
confidence: 81%
“…Mortality of acute AD type A patients with neurological complications reaches 50% in case of further intra-and postoperative complications. Still, patients with neurological deficits, with a favorable early postoperative course, usually recover fully [15]. In our study, preoperative neurological complications were not very frequent (around 7%), but having CVI on admission was associated with more postoperative complications.…”
Section: Discussionmentioning
confidence: 43%
“…Our 30-day and overall mortality rates are similar to these. Two of the most commonly cited preoperative factors that portend worse prognosis are the presence of MPS and renal dysfunction 7,9,11,18 . Berretta et al examined IRAD data and showed that while all forms of MPS were associated with increased mortality, mesenteric ischemia was particularly devastating and carried a 2.5-fold increase in mortality (63% vs. 24%) 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Our 30-day and overall mortality rates are similar to these. Two of the most commonly cited pre-operative factors that portend worse prognosis are the presence of MPS and renal dysfunction 7 , 9 , 11 , 18 . Berretta et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation